Complications of Peripherally Inserted Central Catheters in Adults with Cystic Fibrosis or Bronchiectasis. Issue 3 (May 2015) - Dupont, Christian; Gouya, Hervé; Panzo, Rozy; Hubert, Dominique; Correas, Jean-Michel; Agrario, Line; Chapron, Jeanne; Honoré, Isabelle; Kanaan, Reem; Legmann, Paul; Dusser, Daniel; Vignaux, Olivier; et al.
Background: Peripherally inserted central catheters (PICCs) are increasingly used in patients with cystic fibrosis (CF) or with non-CF bronchiectasis, but little data exist on catheter-related complications in this setting. Methods: Prospective follow-up of consecutive PICCs inserted for intravenous (IV) antibiotics in adults with CF or with non-CF bronchiectasis at Cochin Hospital (Paris, France). Results: Between March 2009 and December 2011, 182 PICCs were prescribed in 117 adults (67 CF and 50 non-CF patients). Ultrasound-guided placement of catheter was successful in 174/182 (95.6%) procedures; no insertion complication occurred. The mean ± SD catheter dwell time was 15 ± 9 days. No catheter-associated bloodstream infection occurred; main complications were symptomatic upper limb deep vein thrombosis (2%), catheter obstruction (18%) and persistent pain after catheter insertion (18%). Patients' satisfaction was high and PICC could be used to perform antibiotic courses in most patients. Conclusions: PICCs were generally safe for performing IV antibiotic courses in patients with CF or non-CF bronchiectasis, but prolonged pain and/or catheter obstruction occurred in approximately 20% of cases.